Pathways to SME Sustainability Integrating: Islamic Finance, Islamic Finance Literature and Government Support for Small and Medium Enterprises - Hasibuan, Beby Kendida; Sadalia, Isfenti; Muchtar, Yasmin Chairunisa; Irawati, Nisrul; Nurfitriani, Wina; Hasibuan, Lailan Syafrina; Isa, Norshamshina Mat (Journal of Ecohumanism, 2024)
MSMEs play a progressively important role in Indonesia’s economic growth, particularly in the context of sharia economic development. The government and Islamic financial institutions (IFIs) have actively supported the empowerment of MSMEs in order to accomplish the Sustainable Development Goals (SDGs). This research aims to conduct a more in-depth analysis of the level of success achieved by these efforts. This research aims to utilize quantitative methods to identify the factors that influence the decision-making process of Micro, Small, and Medium Enterprises (MSMEs) when accessing Islamic financial services. Additionally, it seeks to measure the impact of these factors on the performance of MSMEs. The research results are expected to offer more efficient policy recommendations to enhance the involvement of IFIs in promoting sustainable growth of MSMEs. Research indicates that sharia finance does not have a significant impact on the sustainable performance of MSMEs. However, it is worth noting that sharia financial literacy does have a significant influence on the sustainable performance of MSMEs. Islamic finance exerts a substantial impact on the sustainable performance of micro, small, and medium enterprises (MSMEs). Moreover, the government’s responsibility is to effectively regulate the connection between sharia finance and sharia financial literacy in order to enhance the long-term performance of micro, small, and medium enterprises (MSMEs).